Cooperation-based multi-hop routing protocol for cognitive radio networks. (15th May 2018) - Guirguis, Arsany; Karmoose, Mohammed; Habak, Karim; El-Nainay, Mustafa; Youssef, Moustafa
Abstract: In the scope of cognitive radio networks, typical routing protocols avoid areas that are highly congested with primary users, leaving only a small fragment of available links for secondary route construction. In addition, wireless links are prone to channel impairments such as multipath fading which renders the quality of the available links highly fluctuating. In this paper, we propose Undercover : a multi-hop routing protocol for cognitive radio networks in which we integrate the collaborative beamforming technique with layer 3 routing. Specifically, our protocol revisits a fundamental assumption taken by the state of the art routing protocols designed for overlay cognitive radio networks; this assumption is that secondary users cannot use the spectrum when primary users are using it. In Undercover, we allow a group of secondary users, each with a single antenna, to collaborate together and transmit in the regions of primary users activity. This is done through nulling out transmission at primary receivers via beamforming. Moreover, Undercover is designed to enhance the transmission quality at the secondary destinations whenever possible. To account for the excessive levels of interference typically incurred due to cooperative transmissions, we allow our protocol to be interference-aware. Thus, cooperative transmissions are penalized in accordance with the amount of negatively affected secondary flows. We evaluate the performance of our proposed protocol via NS2 simulations which show that our protocol can enhance the network goodput by a ratio reaches up to 250% compared to other state-of-art cognitive routing protocols with minimal added overhead.